Influence of sesame flour on physicochemical properties of sour milk drinks - Qin, Xuanxuan; Samilyk, Maryna; Luo, Yanghe; Sokolenko, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2021)
This study aimed to investigate the technological properties of kefir fortified with defatted sesame flour (DSF). We have developed a recipe for producing kefir with the addition of 0, 2, 4, 6, 8 % DSF. The physicochemical parameters (pH, titratable acidity) and rheological properties (water-holding capacity, viscosity) of the samples within 28 days of storage were studied. All the samples were stored at a temperature of 4 °C. Nuclear magnetic resonance and chromatographic analysis were performed to determine the optimal shelf life of the product. It was found that fermentation ends on the seventh day of storage, while a low content of free water is observed. The recommended optimal storage time for kefir enriched with DSF is within 14 days. The introduction of 2 % DSF in kefir increases the content of vitamin E by three times (from 0.32 to 0.93 mg/100 g) and the content of proteins – by 1 % (from 3.36 to 4.3 %). The result showed that the pH value decreases with the introduction of DSF and is within the normal range during the entire storage period of the product (from 4.38 to 4.07). In this case, the total titratable acidity increases from 112.07 to 163.52 °T. An increase in viscosity (by 3 Pa∙s) and water-holding capacity (by almost 6 %) is observed with the addition of 2 % additive. Due to the high water-holding capacity and viscosity, dietary fiber content (up to 0.68 %), kefir supplemented with DSF showed high storage stability. The addition of 2 % DSF to kefir can increase the nutritional value and improve the structural stability of the product. DSF is a waste product with a bright prospect for use in the manufacture of fermented milk drinks